2018
DOI: 10.1111/1346-8138.14508
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of dabrafenib and trametinib therapy‐failed advanced melanoma successfully controlled by nivolumab monotherapy

Abstract: Although therapies for advanced melanoma have been greatly improved by the development of immune checkpoint inhibitors and BRAF/mitogen-activated protein kinase kinase inhibitors, there are still many concerns about the administration of these novel drugs. Therefore, to combine these therapies sequentially at appropriate time points of the disease is important. In this report, we report two cases in which dabrafenib and trametinib therapy for advanced melanoma failed but were successfully controlled by nivolum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The patient was a 56‐year‐old Japanese woman who we described in the Journal of Dermatology in 2017, 7 2018, 8 and 2019 9 . Eight months after the administration of ipilimumab in combination with intensity‐modulated radiotherapy, followed by nivolumab monotherapy, follow‐up PET‐CT revealed enlargement of the hilar lymph node with increased standard uptake values (Fig.…”
Section: Case Reportsmentioning
confidence: 99%
“…The patient was a 56‐year‐old Japanese woman who we described in the Journal of Dermatology in 2017, 7 2018, 8 and 2019 9 . Eight months after the administration of ipilimumab in combination with intensity‐modulated radiotherapy, followed by nivolumab monotherapy, follow‐up PET‐CT revealed enlargement of the hilar lymph node with increased standard uptake values (Fig.…”
Section: Case Reportsmentioning
confidence: 99%
“…This report concludes that the absolute serum levels of sCD163 are useful for the prediction of irAEs in melanoma patients, especially in combination with the absolute value of CXCL5 (25). Since serum sCD163 and CXCL5 are, at least in part, derived from CD163+ TAMs that are activated by periostin (24, 26), and chemokine profiles from TAMs are determined by the stimulation of stromal factors (27), spontaneously produced TAM-related factors could be detected in serum from melanoma patients (17, 25, 27). Notably, CD163+ M2 macrophages could be activated by periostin, leading to the production of characteristic chemokines, such as CXCL5, CXCL10, and CCL22, (28) that are correlated with recruitment of both immunosuppressive cells and immune-reactive anti-tumor cells (25).…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al reported that, compared to patients with stable disease, advanced melanoma patients had increased levels of IL-1β and CXCL10 in the serum associated with accumulation of monocytic (Mo)-MDSCs and Tregs in peripheral blood, which correlated with the progression-free survival of these patients (16). In addition, other reports also suggested that serum CXCL10 levels were correlated with disease activity in advanced melanomas (17) and angiosarcomas (18). These reports suggested that serum CXCL10 levels may represent disease activity in advanced melanoma.…”
Section: Introductionmentioning
confidence: 86%
“…The patient was a 56‐year‐old Japanese woman who we described in the Journal of Dermatology in 2017 and 2018 . One year after the administration of nivolumab at 2 mg/kg every 3 weeks, her serum alanine aminotransferase/aspartate aminotransferase suddenly increased (263/82 IU/L).…”
Section: Case Reportsmentioning
confidence: 99%